Components of Metabolic Syndrome in Youth With Classical Congenital Adrenal Hyperplasia - Kim, Mimi S.; Fraga, Nicole R.; Minaeian, Nare; Geffner, Mitchell E. (Frontiers in Endocrinology, 2022)
Classical congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency is the most common primary adrenal insufficiency in children, involving cortisol deficiency, hyperandrogenism, and cardiometabolic risk. Prior studies have reported that youth with classical CAH have a higher prevalence of the components of metabolic syndrome: obesity, hypertension, elevated fasting blood glucose, and dyslipidemia. Yet, the incidence of the complete metabolic syndrome itself in children and adolescents with CAH is relatively rare. Traditional cardiometabolic risk factors can surface early in children with classical CAH, and continue to present and evolve over the lifetime, although it is only recently that reports of Type 2 diabetes and adverse cardiac events have begun to surface in adults affected by this condition. The pathophysiology underlying the increased prevalence of cardiometabolic risk factors in patients with CAH is not well-understood, with disease treatments and androgen excess having been studied to date. The aim of this review is to evaluate the recent literature on traditional cardiometabolic risk factors in youth with classical CAH, and to consider non-traditional risk factors/biomarkers for subclinical atherosclerosis, inflammation, and insulin resistance. A better understanding of these traditional and non-traditional risk factors in youth with CAH could help guide treatment options and prevent the onset of metabolic syndrome in adulthood, reducing overall patient morbidity.